Desenvolvimento e estudo da estabilidade de nanoemulsões do tipo óleo em água com óleos vegetais - Rosani, Leandro (2011)
A low energy emulsification method was used to prepare o/w emulsions of sweet almond or Brazil nut oils stabilized by Tween 80 and Span 80. Stable nano emulsions with droplet size of 160 nm and 270 nm were obtained for almond and Brazil nut oils, respectively, under critical hydrophilic lipophilic balance (HLB). A correlation between emulsions viscosity and particle size allows a precise HLB determination for the oils. The main destabilization mechanism for the emulsions prepared with sweet almond oil was found to be Ostwald ripening that change to coalescence for the emulsion with oil content higher than 10% w/w and HLB higher than 10.